Evaluation of cardiac repolarization inhomogeneity in children with type 1 diabetes mellitus - İlknur Elifoğlu; Rahmi Özdemir; Veysel Nijat Baş; Damla Geçkalan; Emine Değirmen Şişman (Trends in Pediatrics)
Objective: Type 1 diabetes mellitus is the most common endocrine-metabolic disease in childhood, which progresses with insulin deficiency and can cause serious cardiovascular complications. Atrial and ventricular arrhythmias are important cardiovascular complications of diabetes. In this study, cardiac repolarization inhomogeneity in children with Type 1 diabetes mellitus was evaluated electrocardiographically.